HUBUNGAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN SERVIS ATAS PERMAINAN SEPAK TAKRAW - Muhammad Rusli; Suhartiwi Suhartiwi; Heriansyah Heriansyah (JURNAL EDUSCIENCE (JES), 2022)
This study aims to determine the relationship leg muscle power and service ability in the game of sepak takraw. The population in this study were all 31 participants of the takraw game at SMA Negeri 1 Kontukowuna. The sampling technique used was saturated sampling technique or total sampling, namely all members of the population used as samples, so that the sample amounted to 31 people. The leg muscle power instrument used a standing broad jump test and the service ability instrument for the game of sepak takraw used the sepak takraw service test. Based on the data analysis, it can be concluded that there is a significant relationship between leg muscle power and service ability for the student's sepak takraw game, where rxy = 0.49 > rtable (31:0.05) = 0.355 with a coefficient of determination r2 = 0.24 or 24 % means that the leg muscle power makes a big contribution